Beyond the Womb: Reconceiving Motherism as an Ethic of Rahmah in Islamic Theology - Umami, Rizka Hidayatul (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2025)
This article provides a brief discussion of the reconceptualization of ibuism. It attempts to reread the narrative of women's domestication, disguised as glorification, while restricting women's access to other spaces. Specifically, this article aims to deconstruct the meaning of ‘ibuism.’ The author, in turn, seeks to reinterpret the narrow narrative of ibuism, shifting its understanding to a paradigm of ethics of care. The method used in writing this article is a literature study, where books and journal articles that focus on discussing ibuisme, domestification, and gender roles are the main sources. Through a theological analysis approach, this research finds that the core values attached to the mother figure, particularly rahmah (compassion) and tarbiyah (nurture), are not attributes tied solely to gender or the womb. Both are universal sources of ethics. Meanwhile, the domestication of women under the guise of motherhood is a theological distortion. Conversely, co-parenting and men's involvement in the domestic sphere are ethical imperatives. Ultimately, this re-conceptualization not only aims to free women from the shackles of narrow nature but also invites men to participate fully in the ethics of care to realize a fair family and maslahah.